Perfil de progesterona em macacos-da-noite (Aotus azarai infulatus) em cativeiro - Coutinho, Leandro Nassar [UNESP] (2014)
Owl Monkeys are considered excellent experimental models and can contribute to the development of biotechnologies of reproduction in primates. Monitoring the reproductive cycle is a basic procedure, however complex in wild animals. Noninvasive methods has been developed to assess the reproductive hormonal profile of these animals expanding knowledge on reproductive physiology of primates in captivity and the wild. This study aims to monitor follicular activity and fecal progesterone levels to increase knowledge about reproductive physiology of this species. 12 adult females belonging to the breeding colony of owl monkeys of CENP were used. The study was performed using the ultrasound examination of the ovaries and feces collection for monitoring the levels of metabolites of progesterone by enzymeimuneassay. By progesterone assay we may suggest the cycle of the species for the period studied. However, the baseline levels (2.1 ± 0.8 ng/g), mean peak (36.6 ± 8.6 ng/g), mean levels (4.7 ± 1.8 ng/g) and the minimum (0.4 ng/g) and maximum (49.9 ng/g) metabolites of progesterone were determined for the specie in captivity. The determination of the peak and basal levels of progesterone together to the sonographic evaluation are noninvasive and feasible in the evaluation of the estrous cycle in owl monkeys